The Practice Instructor System: Salvation or Illusion in Master’s-Level Social Work Education? - Qin, Keke (International Journal of Social Sciences and Public Administration, 2025)
Although master’s programs in social work claim to prioritize the cultivation of practice-oriented professionals, in reality, they have long been trapped in a dilemma of "emphasizing theory while neglecting practice." As a result, graduates often find themselves ill-equipped to address complex social issues. The practice instructor system has been heralded as a potential panacea for bridging this gap. However, its implementation has repeatedly faltered due to a lack of qualified mentors, institutional deficiencies, and structural limitations. Adopting a critical perspective, this paper questions the effectiveness of the current model of social work education at the master’s level and directly confronts the multiple constraints facing the practice instructor system. Despite the numerous challenges, the paper argues that the practice instructor system is not an unattainable ideal. With targeted institutional design and well-calibrated incentive mechanisms, it holds significant potential to become a catalyst for substantive reform in social work education.